The Analysis of the Community Food Barns Role In Maintaining Food Reserves Availability in Buay Pemuka Peliung Sub-District, East OKU District - Putra, Aidin Eka; Munajat, Munajat; Sari, Yunita (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
This study aimed to determine the role of community food barns in maintaining food reserve availability in Buay Pemuka Peliung Sub-District, East OKU District, and to identify the factors influencing household food availability among farmers in the same area. The research employed a quantitative descriptive method and utilized multiple regression analysis for data evaluation. The findings indicated that community food barns are crucial in ensuring food security for farmers in Buay Pemuka Peliung Sub-District. Specifically, the food barns serve three main functions: storing food, mitigating food shortages during crop failures or droughts, and increasing group income among farmers. The presence of these food barns has proven to be highly beneficial, providing secure storage for farmers' harvests. Moreover, the study identified several factors influencing household food availability among farmers, including land area (X1), income (X2), paddy prices (X3), number of family members (X4), farmer's age (X5), and education level (X6). Among these, the variable that had the most significant impact on household food availability was the land area, with a partial regression coefficient (beta coefficient) value of 3.099.